Pengaruh Price Discount, Bonus Pack, dan Cashback terhadap Impulse Buying Produk di Marketplace Shopee - Yoritiara, Sylvia; Wijono, Djoko (Jurnal Manajemen Strategis: Jurnal Mantra, 2025)
Modernization and ease of life have become direct consequences of rapid technological progress. The surge in internet use, particularly in e-commerce, has become a major driver of economic growth. Shopee is the largest e-commerce platform in Indonesia, standing out with various promotional strategies, including price discounts, bonus packs and cashback. A quantitative approach using accidental sampling techniques was used for 100 respondents with the aim of finding out the impact of price discounts, bonus packs and cashback on impulse buying. It was found from the research results that price discounts, bonus packs and cashback had an impact of 22.6% on impulse buying on the Shopee marketplace. Partially, only the bonus pack has a significant impact on impulse buying on the Shopee marketplace.